Introduction of land market: current issues and development prospects - Novakovska, I.; Skrypnyk, L.; Ishchenko, N. (Land Management, Cadastre and Land Monitoring, 2021)
The peculiarities of the free market of agricultural lands are described. The consequences of opening the land market in terms of economic, land and legal components in the system of land relations are presented. The list of conditions for the purchase and sale of agricultural land is highlighted. The specifics of the functioning of the free market of agricultural lands are substantiated. The characteristic of basic normative-legal acts in the sphere of functioning of the land market is given. A comparative analysis of the current state of purchase and sale of land by farms and agricultural holdings. A comparison of the indicators of the number of concluded agreements of purchase and sale of agricultural land, the average value of rent per 1 hectare of land, respectively, by region and price fluctuations per 1 hectare of land when concluding purchase and sale agreements. The foreign experience of land market function with the detailing of the factors influencing the further development is analyzed. In particular, the problems and needs in the functioning of the land market of Poland, Brazil, the United States and the United Kingdom are considered. The possibility of introducing an electronic system such as EMBRAESP, which monitors the main indicators of the efficiency of the urban real estate market, together with city legislation, land regulations and large public works projects that may affect the behavior of real estate markets. Key words: land relations, land market, land lease, land legislation.